Community-based cognitive and language stimulation through therapeutic group therapy for toddlers in an urban low-income area: a case report - Mawaddah; Keliat, Budi Anna; Chandra, Yudi Ariesta; Daulima, Novy H.C. (Universitas Gadjah Mada, 2025)
Purpose: Early childhood development is crucial for psychosocial growth, particularly in cognitive and language domains. In resource-limited areas, health promotion through community-based stimulation can bridge service gaps. A community-based approach involving parents and community health workers (CHWs) can effectively promote and prevent health issues in the community. Program description: A structured intervention using therapeutic group therapy (TGT) was implemented for toddlers aged 1–2 years in Batu Tulis Village, South Bogor, in December 2024. Implementation process: The program involved collaboration among mental health nursing students, mothers, health cadres, and local health workers. Activities focused on enhancing cognitive and language abilities. The intervention consisted of 30 to 45-minute stimulation sessions facilitated by mental health nursing students. Outcomes and observations: Improvements were observed in children's vocabulary, understanding of basic concepts, and social interaction. The evaluation was conducted through qualitative observation, structured interviews with parents, and the use of child development indicators based on the standards of the Indonesian Ministry of Health. Parents reported that their children's communication and independence in daily routines had increased. Implications for health workers: The case highlights the vital role of community health actors and mental health professionals in promoting early childhood development through straightforward and replicable interventions. This program is relevant for integration into primary health services and posyandu activities as part of the community's promotive and preventive strategy. Conclusion: Community-based cognitive and language stimulation intervention can potentially support young children's psychosocial development.